Commercial Insurgencies in the Networked Era: The Revolutionary Armed Forces of Colombia. (2019)
This book examines the Revolutionary Armed Forces of Colombia (FARC) as a commercial insurgency through the network-complex paradigm of insurgency. Countering traditional perspectives of the group, it proposes new and comprehensive explanations for the FARC’s presence in Latin America. Existing narratives have portrayed the FARC as a terrorist, narco-terrorist, or criminal organization – a narrative popularized by the government offensive conducted by the Colombian state during the last couple of decades. In contrast, this book goes beyond simplistic perspectives of the FARC and instead studies the group in relation to the network-complex paradigm of insurgency.